Morphological characterization and ecotypic classification of olive varie-ties in Bordj Bou Arreridj, Algeria - Ahmed, Saad; ElHouda, Sebbane Nour; Madjid, Seghiri Abdel; Djamila, Madani (Future Science, 2025)
The aim of this research is to establish the phenotypic variation that exists in the olive varieties of Olea europaea L. in the Bordj Bou Arreridj region of Algeria. The study examined 18 olive varieties from 20 farms, focusing on the morphological characterisation of fruits, leaves, and endocarps using standard descriptors and precise measurement tools. Significant coefficients of variation were ob-served for the traits studied, indicating substantial differences among the varieties. The highest variability was found in fruit weight, with a coefficient of variation (CV) of 48.60%, while leaf length demonstrated the lowest CV at 9.77%. Principal Component Analysis (PCA) primarily distinguished three different ecotypic groups based on fruit and endocarp size and shape parameters. The Bray-Curtis similarity analysis revealed compositional similarities among some of the local variants, providing insights into their po-tential genetic relationships. Notably, the study reports the presence of the rare Leucocarpa variety, which had not been previously doc-umented in Algeria. This discovery highlights the importance of thorough regional surveys in uncovering hidden biodiversity. The findings reveal a rich agro-morphological genetic variation in olive ecotypes in the region, which is valuable for genetic conservation efforts and breeding research. This diversity could potentially be exploited to develop cultivars with improved traits such as disease resistance, oil quality, or adaptation to specific environmental condi-tions. Our classification enables targeted breeding, prioritized conser-vation, and optimized cultivation practices, supporting the devel-opment of resilient, locally-adapted varieties and the preservation of valuable genetic resources in the region's olive industry.